Conceptual science and beyond : general biology 1 : a worktext for senior high school - Pineda, Maria Cielo Herminia S.; Yap, Maria Corazon C. (Quezon City : Brilliant Creations Publishing, Inc., 2017)
"This textbook is designed for Senior High School students under STEM strand, aiming to equip them with the necessary competencies as indicated in the DepEd Curriculum guide for the STEM specialized subject Biology 1. With this in mind we have meticulously enriched every lessons in order for the students to have a relevant and enjoyable learning experiences."
Includes glossary and bibliography.
English text.
Keywords: Biology